Indios muzicos do século XVIII: a banda indígena do Embu (1783-1829) - Goncalves, Daniel Issa [UNESP]; Castagna, Paulo Augusto [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2024)
An indigenous mission since the 17th century, the village of Embu was characterised by the presence of several musicians among its inhabitants. According to D. Duarte Leopoldo e Silva, archbishop of S & atilde;o Paulo, there was a musical ensemble in the village formed by indigenous people of the Guaianazes ethnic group that was considered the best in the region, if not the only one, and was an obligatory part of all great solemnities of the environs, and even as far as Itanha & eacute;m and Bragan & ccedil;a. Considering the relevance of the subject for the historiography of music in Brazil, we looked into the historical censuses of S & atilde;o Paulo (from 1765 to 1850) searching for musicians in Embu. Then, we compared the names obtained with those on records of the Embu Parish, to find family registers of the identified individuals in order to reconstruct the biography of these forgotten indigenous musicians.
Keywords: Indigenous Musicians; Colonial Music; Embu; Jesuitic Missions; History of Music in Brazil